Sukūk development and income inequality - Wahyu, Jatmiko (2023)
This paper investigates the link between sukūk development and income inequality by scrutinizing twenty-two countries’ data from 1995 to 2019. We employ the two-stage Fractional Regression Model to illustrate that sukūk issuance is associated with increased income disparity. This result is attributed to the sukūk design ignoring credit market frictions. This rationalizes the sukūk-inequality nexus in light of the ethical objectives of Islamic law. We argue that reinforcing property rights by mitigating the ill effects of excessive risk-taking (i.e., gharar) and endemic agency costs of debt (i.e., ribā) in our ethical framework can improve sukūk’s role in socio-economic development.